Long non-coding RNA BX357664 inhibits gastric cancer progression by sponging miR-183a-3p to regulate the PTEN expression and PI3K/AKT pathway. (April 2021) - Liang, Li-Chuan; Liu, Lin-Qing; Liu, Liu; Liu, Dong-Liang; He, Yi-Ren; Wan, Xiao; Zhu, Zhi-Qiang; Zhang, Bao-gui; Liu, Shao-Jun; Wu, Huo; Hu, Lei
Abstract: Lately, long non-coding RNA (lncRNA) is recognized as a key regulator of gastric cancer (GC) which has aroused great interest in the fields of medicine, toxicology, and functional food. Studies related to LncRNA expression microarray data indicate that BX357664 is down-regulated in GC specimens. However, the expression pattern and molecular mechanism of BX357664 in GC have not been studied so far. The purpose of this study was to investigate the expression of lncRNA BX357664 in GC and its function in GC cell lines. Real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect the level of BX357664 in 50 pairs of cancer tissues and adjacent non-cancer tissues collected from GC patients. It was found that BX357664 level was lowered in cancer specimens than adjacent non-cancer tissues and correlated with tumor size and TNM stage. Also, we used cell counting kit 8 (CCK8), cell clone formation assay and transwell assay, which affirmed that up-regulation of BX357664 inhibited the proliferation, migration, and invasion of GC cells, but promoted apoptosis. In the dual-luciferase report analysis, BX357664 acted as a miR-183–3p ceRNA to target and regulate the expression of PTEN and affect the PI3K/AKT pathway. These results indicate that BX357664 can inhibit the proliferation and metastasis of GC through the miR-183–3p/PTEN/PI3K/AKT pathway, which may serve as potential targets for the treatment of GC in the future. Highlights: LncRNA BX357664 is down-regulated in GC tissues. LncRNA BX357664 can inhibit the proliferation, migration in GC cells. LncRNA BX357664 can target and regulate the expression of PTEN.